THE INFLUENCE OF SIGNLE NUCLEOTIDE POLYMORPHISMS ON THE THERAPEUTIC EFFECT OF ANTIRETROVIRAL DRUGS - Obradović, Božana (Medicinski podmladak, 2023)
Background: Availability of combined antiretroviral therapy (cART) has significantly improved the prognosis of HIV infection. In order to control the infection, patients chronically take different groups of antiretroviral drugs, which can lead to numerous unwanted and toxic effects, as well as potential interactions with other co-administered medications and food. Most available antiretroviral drugs are metabolized by cytochrome P450 enzymes and excreted through various transport proteins, which can undergo multiple genetic changes. Single nucleotide polymorphisms (SNPs) has been research subject in various fields, including HIV infection. Variations in the genetic makeup of metabolic enzymes and transporters are particularly noteworthy. Objective: The aim of this research was to provide a review and analysis of the most common gene polymorphisms encoding metabolic enzymes and transporters that are essential for the pharmacokinetics of antiretroviral drugs. Methodology: A literature review was conducted by searching the Pub Med and Medline databases from 1998 to 2022. The search was performed using appropriate keywords such as "cytochrome," "antiretroviral," "genotype," "polymorphism," "pharmacogenetic," "pharmacogenomic," "pharmacokinetic," "variant," and "single nucleotide polymorphism," in combination with "human immunodeficiency virus" and "acquired immunodeficiency syndrome." The identified literature was then reviewed and analyzed. Results: The clinically most relevant polymorphisms affecting the therapeutic efficacy of antiretroviral drugs include HLA-B5701, CYP2B6 polymorphisms corelated with high plasma concentrations of efavirenz, and UGT1A16 and *28 responsible for individual variations in the pharmacokinetics of dolutegravir. Conclusion: Genetic variations, including variations in individual nucleotides, as well as other factors such as gender, coexisting medical conditions, and patient-related factors, plays a significant role in therapeutic response. Understanding these factors is of crucial importance for personalized approaches to the treatment of HIV infection and the optimization of therapeutic outcomes.